Roles of c-type cytochromes in respiration in Neisseria meningitidis - Manu Deeudom (2018)
Three c-type cytochromes were identified in Neisseria meningitidis, based on predictions from genome sequences, that were hypothesized to be involved in electron transport to terminal electron acceptor reductases for oxygen (the cytochrome cbb3 oxidase) and nitrite (the nitrite reductase, AniA). Mutants were generated by allelic exchange with disrupted copies of the genes encoding these cytochromes and the phenotypes of the resultant mutants analysed. It was found that cytochrome c5 is required for in vivo nitrite reductase activity, whereas cytochromes cx and c4 are both required for efficient growth using oxygen as an electron acceptor. Mutants in cx, c4, and cx+c4 have a decreased capacity to reduce oxygen, but there is a background oxygen-reduction activity, indicating that there may be other routes for electron transfer from the cytochrome bc1 complex to the cytochrome cbb3 oxidase, whereas cytochrome c5 appears to be the sole route of electrons to the nitrite reductase in N. meningitidis. Interestingly, cytochrome cx is highly similar to a domain of copper nitrite reductases from various proteobacteria, whereas cytochrome c5 has high identity with a domain of the cytochrome cbb3 oxidase of Neisseria gonorrhoeae, yet these two proteins function in oxygen respiration and nitrite respiration, respectively. This highlights a limitation of predicting protein function from similarity to known proteins, i.e. very closely related protein domains in different organisms can have different redox partners. © 2008 SGM.